Research progress and strategy of FGF21 for skin wound healing - Lin, Shisheng; Tang, Lu; Xu, Nuo (Frontiers in Medicine, 2025)
Fibroblast Growth Factor 21 (FGF21), a pivotal member of the fibroblast growth factor family, exhibits multifaceted biological functions, including the modulation of pro-inflammatory cytokines and metabolic regulation. Recent research has revealed that in impaired skin tissues, FGF21 and its receptors are upregulated and play a significant role in accelerating the wound healing process. However, the clinical application of FGF21 is severely limited by its short in vivo half-life: this factor is often degraded by enzymes before it can exert its therapeutic effects. To address this limitation, the transdermal drug delivery system (TDDS) has emerged as an innovative approach that enables sustained drug release, significantly prolonging the therapeutic duration. Leveraging genetic recombination technology, research teams have ingeniously fused FGF21 with cell-penetrating peptides (CPPs) to construct recombinant FGF21 complexes. These novel conjugates can efficiently penetrate the epidermal barrier and achieve sustained and stable pharmacological activity through TDDS. This review systematically analyzes the potential signaling pathways by which FGF21 accelerates skin wound repair, summarizes the latest advancements in TDDS technology, explores the therapeutic potential of FGF21, and evaluates the efficacy of CPP fusion tags. The manuscript not only proposes an innovative paradigm for the application of FGF21 in skin injury treatment but also provides new insights into its use in transdermal delivery, marking a significant step toward overcoming existing clinical therapeutic challenges. From a clinical medical perspective, this innovative delivery system holds promise for addressing the bioavailability issues of traditional FGF21 therapies, offering new strategies for the clinical treatment of metabolism-related diseases and wound healing. With further research, this technology holds vast potential for clinical applications in hard-to-heal wounds such as diabetic foot ulcers and burns.